Ways of attracting customers in the commercial banks - Kravchenko, V.; Mogiley, A.; Кравченко, В. П.; Могилей, A. O. (КНТУ, 2013)
The article considers the deposit policy. The use of banks of price and non-price methods of attraction of free money resources. Proposes to introduce a tool - «deposit with interest payment in advance» and the direction of reducing the risk of early termination of the deposit agreement. У статті розглянуто депозитну політику. Використання банками цінових та нецінових методів залучення вільних грошових ресурсів. Запропоновано впровадити інструмент - «депозитний внесок з виплатою відсотків авансом» та напрямки зниження ризику дострокового розірвання депозитного договору.
Шляхи залучення клієнтів у комерційних банках
Keywords: deposit; credit; credit policy; commercial banks; competition; resources; management methods; tools deposit policy; penalties; депозит; кредит; депозитна політика; комерційні банки; конкуренція; ресурси; методи управління; інструменти депозитної політики; штрафні санкції